Risk factors for enteral feeding intolerance in critically ill patients: an updated systematic review and meta-analysis - Si Wang; Yang He; Jing Yi; Liyan Sha (BMC Gastroenterology)
Abstract Background This meta-analysis aimed to evaluate the factors influencing enteral nutrition feeding intolerance in critically ill patients. Methods PubMed, Embase, Scopus, Medline, Web of Science, CNKI, VIP, WanFang and CBM databases were searched. A sensitivity analysis was carried out to explore the influence of individual studies on the pooled results of the included studies using a fixed-effects model or a random-effects model. The pooled results were expressed as the odds ratios (ORs) and 95% confidence intervals (Cls). Finally, a funnel plot was developed to describe the publication bias. Results Twenty-three studies involving 30,688 participants were included. Meta-analysis results showed that age, body mass index (BMI), APACHE II score, renal insufficiency, digestive system diseases, hypoproteinemia, sepsis, and post-pyloric feeding, starting feeding within 48 h, feeding pattern, nutritional formula, sedative drugs, vasoactive drugs, use of more than two antibiotics, oral potassium preparation, mechanical ventilation, days of mechanical ventilation, length of ICU stay, and mortality were the influencing factors of enteral nutrition feeding intolerance in critically ill patients. The results of the sensitivity analysis showed that the direction of the pooled effect size did not change after excluding each study one by one, suggesting that the results of the meta-analysis were robust. Conclusions According to the influencing factors, medical staff can pay attention to the high-risk patients at ICU admission to reduce the risk of feeding intolerance.